Rural-urban migration, welfare and employment: Comparing results from Thailand and Vietnam - Ulrike Grote; Hermann Waibel (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2017)
This paper compares empirical findings on the motivation and welfare impacts of rural-urban migration from two comprehensive case studies conducted in Thailand and Vietnam. Panel data of around 4,000 rural households and tracking surveys of close to 1,000 migrants are used from the two countries. The studies find that outcomes depend to a large extent on the development status of the country. Rural households consider outmigration mostly as a livelihood support strategy. Given the scarcity of employment opportunities in the rural areas, migrants see themselves forced to look for jobs in the cities. Interestingly, most migrants perceive themselves to be better off in the cities. The rural households left behind benefit from migration as the remittances tend to have positive income growth effects. The research confirms the calls for improved social protection for migrants in urban areas and for quality schooling in the rural areas.
Keywords: O15; Q56; R23; 330; Migration; Poverty; Livelihoods; Employment quality; Vietnam; Thailand